Adolescents' Attitude toward HIV/AIDS Prevention in Yogyakarta - Tiranda, Meysa; Setiyawati, Nanik; Rahmawati, Anita (Kesmas, 2018)
Acquired immunodeficiency syndrome (AIDS) is the second leading cause of death in adolescent groups in the world. In Indonesia, the rate of human immunodeficiency virus (HIV)-infected adolescents increases annually. Yogyakarta, well-known as the education city, has the highest number of HIV/AIDS cases in the productive age group of 20–29 years old, which means that they have been already infected with HIV since teen age. This study aimed to determine influential factors that affect adolescents' attitude toward HIV/AIDS prevention. The study was an analytic survey research with a cross-sectional design. Stratified random sampling was applied to select a sample size of 128 respondents of class XI at Muhammadiyah 3 Yogyakarta Senior High School in 2017. Data were taken by using questionnaires that had been tested for validity and reliability. Data were analyzed by chi-square test and logistic regression. The results revealed that most of the respondents received information on HIV/AIDS from media (47.7%), have a good knowledge level (82%), and support the prevention of HIV/AIDS (96.9%). The source of information and knowledge level had a statistically significant relation with adolescents' attitude toward HIV/AIDS prevention. Knowledge level is the most influential factor to adolescents' attitude toward HIV/AIDS prevention (p value = 0.006, PR = 1.199; 95% confidence interval = 1052–1367).